Dermonutrition and akin care: the Essensis ® case - Lassel Taous (Oléagineux, Corps gras, Lipides, 2008)
The skin is an outward sign of inner health and well being. Providing protection is certainly one of the most important function of the skin functions. As a protective barrier, the skin must prevent water loss and protect against pathogen and foreign substances entering the body. One of the primary layers that provide this protection is the stratum corneum (SC). Lifestyle changes such as ageing, and environmental factors, in particular cold weather, can impair the functioning of this barrier through alterations to the composition of the lipids which make up the SC. Under such circumstances, transepidermal water loss levels may be elevated and the natural moisture barrier may be more susceptible to irritation or to the development of dry skin. It is now well established that good skin condition is dependent upon nutrients in the diet. Interestingly some nutritional factors could help to improve skin barrier such as fatty components (fatty acids, vitamin E) that helps to improve the natural moisture barrier of the skin and or keratinocyte cellular differentiation which in vitro improve SC barrier function. Essensis is a fermented dairy product specifically formulated with borage oil, green tea extract and vitamin E to improve skin barrier function as part of a healthy diet. Essensis addresses the healthy population – globally and from a dermatological perspective.